The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00134-002-1508-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two depths of prolonged neuromuscular blockade induced by cisatracurium in mechanically ventilated critically ill patients

Abstract: When a prolonged curarization is decided upon in an ICU patient, a blockade at 2/4 at TOF at orbicularis oculi has similar effects on respiratory parameters as a blockade at 0/4, allowing a decrease in total administered doses and a shortening of the recovery of muscle strength after cessation of infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 19 publications
0
27
0
2
Order By: Relevance
“…Rudis et al 26 reported that lower doses of NMBAs were used and recovery from paralytic agents was faster in patients randomized to TOF-guided therapy, whereas 2 other studies 27,28 showed no difference between groups in total paralysis time, recovery time, and amount of drug used. In a randomized controlled trial 29 of 102 patients with ARDS who were given cisatracurium, Figure 4 Degree to which baseline factors or concurrent therapies are perceived to alter the risk profile of neuromuscular blocking agents. This study had several possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Rudis et al 26 reported that lower doses of NMBAs were used and recovery from paralytic agents was faster in patients randomized to TOF-guided therapy, whereas 2 other studies 27,28 showed no difference between groups in total paralysis time, recovery time, and amount of drug used. In a randomized controlled trial 29 of 102 patients with ARDS who were given cisatracurium, Figure 4 Degree to which baseline factors or concurrent therapies are perceived to alter the risk profile of neuromuscular blocking agents. This study had several possible limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Coggeshall et al 29 reported a case in which the use of NMBA improved gas exchange. In 102 adult patients in acute respiratory distress with a PaO 2 /FiO 2 Ͻ200, Lagneau et al 35 noted that whatever the level of paralysis (2 or no response to the train-of-4), there was a significant improvement in the PaO 2 /FiO 2 ratio after 30 minutes and after 2 hours of continuous administration of cisatracurium, when compared with before NMBA. 28 Effects of NMBA on Gas Exchange in Patients With ARDS main hypotheses to explain this effect were a decrease in oxygen consumption and a better adaptation to mechanical ventilation as soon as cisatracurium was infused.…”
Section: The Effects Of the Use Of Neuromuscularblocking Agents On Gamentioning
confidence: 97%
“…28 Effects of NMBA on Gas Exchange in Patients With ARDS main hypotheses to explain this effect were a decrease in oxygen consumption and a better adaptation to mechanical ventilation as soon as cisatracurium was infused. The study by Lagneau et al 35 was not designed to analyze the effect of NMBA on gas exchange and there was no control group; each subject was compared before and after NMBA infusion. In a prospective, controlled, randomized, multicenter study, 36 we evaluated the effects of a 48-hour NMBA infusion on gas exchange over a 120-hour time period in 56 patients with ARDS (PaO 2 /FiO 2 Ͻ50 mm Hg with a PEEP of at least 5 cm H 2 O).…”
Section: The Effects Of the Use Of Neuromuscularblocking Agents On Gamentioning
confidence: 99%
“…The effort to improve postoperative respiratory muscle function and avoid respiratory failure begins with surgical and anesthetic planning: minimally invasive techniques 56,116,199 and 215,227 Diaphragmatic dysfunction Minimize diaphragmatic immobility 147,157,228 Respiratory muscle exercise 161 Sasaki et al…”
Section: Strategies To Prevent Postoperative Respiratory Failurementioning
confidence: 99%